1980
DOI: 10.1021/bi00567a041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nocodazole on structures of calf brain tubulin

Abstract: The interaction of nocodazole with calf brain tubulin was studied to determine the effect of such interaction on the structure of tubulin. The effect of nocodazole on the self-association of tubulin was monitored by turbidity measurements and velocity sedimentation. Sedimentation patterns indicate that nocodazole neither induces tubulin to undergo self-association to form higher orders of aggregate nor does it perturb the equilibrium of the reaction leading to the formation of 42S double-ring structures althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
1

Year Published

1983
1983
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 31 publications
5
49
0
1
Order By: Relevance
“…Aliquots were kept at -20°C and diluted to final concentrations in PEM buffer [0.1 M piperazine-N,N'-bis(2-ethanesulfonic acid), pH 6.9,2 mM EGTA, 1 mM MgSO4I for in vitro studies or in cell culture medium for in vivo studies. These working dilutions were kept on ice and used within 4 h to minimize the likelihood of the nocodazole precipitating out of solution (Lee et al, 1980). Porcine brain tubulin and axoneme fragments from Strongylocentrotus purpuratus sperm were prepared as described previously (Vasquez, et al 1994).…”
Section: Materials and Methods Stock Solutions And Protein Purificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Aliquots were kept at -20°C and diluted to final concentrations in PEM buffer [0.1 M piperazine-N,N'-bis(2-ethanesulfonic acid), pH 6.9,2 mM EGTA, 1 mM MgSO4I for in vitro studies or in cell culture medium for in vivo studies. These working dilutions were kept on ice and used within 4 h to minimize the likelihood of the nocodazole precipitating out of solution (Lee et al, 1980). Porcine brain tubulin and axoneme fragments from Strongylocentrotus purpuratus sperm were prepared as described previously (Vasquez, et al 1994).…”
Section: Materials and Methods Stock Solutions And Protein Purificationmentioning
confidence: 99%
“…It is still widely used to study MT-dependent processes because of its ability to rapidly depolymerize MTs in vivo when administered at micromolar concentrations. Early studies demonstrated that, at concentrations equal to or greater than those of tubulin, nocodazole inhibits tubulin polymerization in vitro (Hoebeke et al, 1976;Friedman and Platzer, 1978;Ireland, 1979;Lee et al, 1980) and in vivo . Cultured cells treated with high concentrations of nocodazole quickly depolymerize their MTs and are prevented from proceeding through mitosis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excitation and emission wavelengths were 488 nm and 505 nm for BODIPY FL-C5, and 543 nm and 580 nm for TAMRA-succinimidyl ester, respectively. Nocodazole (methyl-(5-[thienylcarbonyl]-1 H-benzimidazol-2-YL) carbamate; Sigma Aldrich, St. Louis, Missouri), an agent that interferes with structure and function of microtubules (Lee et al, 1980), was added to the media (5 g/ml) 30 minutes before the addition of apoptotic bodies to modulate phagocytosis.…”
Section: Phagocytosismentioning
confidence: 99%
“…Microtubule polymerization was modulated by either a depolymerization protocol using nocodazole or colchicine (Sigma Chemical Co.), or by promoting microtubule assembly with taxol, a plant-derived drug that has been reported to enhance microtubule assembly and stabilize microtubules against depolymerizing conditions (Garland, 1978;Schiff et al, 1979;Lee et al, 1980 (Loeb et al, 1985;Pollock et al, 1991;Ishii et al, 1991;Nunokawa et al, 1993 collected and the acid-extracted cultures were solubilized in 1.0 N NaOH. The HCl extract was directly analysed for cyclic GMP by radioimmunoassay using the automated Gammaflow system and the protein concentration of the NaOH-solubilized samples was determined, as described by Marczin et al (1992Marczin et al ( , 1993.…”
Section: Modulation Of Microtubule and Microfilament Assemblymentioning
confidence: 99%